Business Planning Training For Msme In Ujung Padang and Bosar Maligas Districts - Robert Tua Siregar; Darwin Lie; Sofiyan Matondang; Lora Ekana Nainggolan (International Journal Of Community Service, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economic growth because they are the largest absorbers of labor and a significant contributor to GDP. However, many MSME actors are still constrained by the lack of knowledge in business planning and management. In Ujung Padang and Bosar Maligas Districts, the potential of MSMEs is quite high in the culinary, trade, and handicraft sectors. The observation results show that most MSMEs are still operating traditionally without a clear business plan, thus hindering business development, access to financing, and competitiveness. To answer these problems, the service team held a "Business Planning Training for MSME Actors" to improve understanding and skills in preparing an applicable business plan. This training is expected to be able to encourage the development of MSME businesses in a more targeted and sustainable manner.